Sustaining paddy self-sufficiency and land demands in Sabah, Malaysia: a structural paddy and rice econometric model analysis - Wong, Kelly Kai Seng; Shamsudin, Mad Nasir; Sharifuddin, Juwaidah; Mohamed, Zainal Abidin (IJFAEC, 2017)
The objective of this study is to construct an econometric commodity model in order to forecast the long term rice production performance of the state of Sabah, Malaysia. The baseline projection shows that the Sabah rice self-sufficiency is estimated to achieve approximately 38% in the next 10 years due to the scarcity of the suitable land bank allocate for paddy cultivation. In order to achieve 60% of targeted rice self-sufficiency level (SSL), the size of land for paddy cultivation must be increased in Sabah. Based on the scenario simulation projection result, the expansion of paddy cultivation area will contribute a positively to the industrial rice production and consequently achieving the expected 60% of SSL by the end of 2024. In a nutshell, the state government of Sabah possess state autonomy on the land management, thus the state government plays a significant key role on promoting the local rice self-sufficiency level in the long-term period.